Kajian konsep utama dalam studi al-qur'an: jam’ al-qur’an - Baidlowi, Muhammad Rifqi (Maliki Interdisciplinary Journal, 2025)
Jam’ al-Qur’ān refers to the process of collecting and codifying the divine revelations sent to Prophet Muhammad (PBUH) until they were standardized in an official mushaf. This process took place in three major stages: during the time of Prophet Muhammad (PBUH), the caliphate of Abu Bakr As-Siddiq, and the caliphate of Uthman ibn Affan. During the Prophet’s lifetime, the Qur’an was preserved through the memorization of his companions and recorded on various materials, such as palm leaves, bones, and animal skins. After the Prophet’s passing, particularly following the deaths of many Qur’an memorizers in the Battle of Yamamah, Caliph Abu Bakr initiated the first codification, led by Zaid ibn Thabit, producing a mushaf that was later entrusted to Hafsah bint Umar. During the time of the Prophet Muhammad SAW, the Qur'an had not been codified in one mushaf, but was memorized by friends and written on various simple media, such as date palm fronds, bones and animal skins. The Prophet SAW himself directed the writing of the revelation, ensured the accuracy of the companions' memorization, and determined the order of the verses in each surah based on instructions from the Angel Gabriel.